Event branding: combating cyberbully / Nur Fitrah Thulan Thuraichelvam - Thuraichelvam, Nur Fitrah Thulan (Faculty of Art and Design, 2020)
Cyberbullying is an extension of traditional bullying acted out in a virtual world of user anonymity.